1936
DOI: 10.1021/ja01302a046
|View full text |Cite
|
Sign up to set email alerts
|

The Reaction between α-Ketonic Acids and α-Amino Acids

Abstract: Two grams of retenediphenic anhydride was dry distilled, yellow vapors coming over accompanied by carbon dioxide. The distillate soon solidified to a yellow, crystalline material; yield, 1.5 g. (90%). From 95% ethanol it appeared as long, flat, sulfur-yellow prisms, m. p. 89-90°( corr.). Mixed with an equal amount of an authentic specimen of retene ketone of m. p. 88-89°( corr.), it melted at 89-90°( corr.).When retenediphenic acid or an intimate mixture of its anhydride and soda lime were distilled, retene k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0

Year Published

1939
1939
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(15 citation statements)
references
References 0 publications
2
13
0
Order By: Relevance
“…A 12% yield of alanine was reported with optimum yields of products observed within a pH range of 1.9 to 2.6. The proposed mechanism is, for the most part, consistent with that suggested by Herbst and Rittenberg in that the transamination process does not involve an equilibrium between isomeric imine intermediates since no keto acid product was reported. Instead, it was suggested that the process involved a concerted decarboxylation and double bond migration; the cyclic transition state illustrated in Figure was proposed for this step…”
Section: Introductionsupporting
confidence: 87%
See 1 more Smart Citation
“…A 12% yield of alanine was reported with optimum yields of products observed within a pH range of 1.9 to 2.6. The proposed mechanism is, for the most part, consistent with that suggested by Herbst and Rittenberg in that the transamination process does not involve an equilibrium between isomeric imine intermediates since no keto acid product was reported. Instead, it was suggested that the process involved a concerted decarboxylation and double bond migration; the cyclic transition state illustrated in Figure was proposed for this step…”
Section: Introductionsupporting
confidence: 87%
“…Specifically, α‐aminophenylacetic acid produced a near quantitative yield of benzaldehyde, alanine, and CO 2 upon reaction with pyruvic acid. A mechanism involving initial imine formation followed by double bond migration via a stepwise 2‐azaallylic proton transfer and subsequent decarboxylation was proposed . It was also reported that while the decarboxylation process proceeded under acidic conditions, it was inhibited under basic conditions.…”
Section: Introductionmentioning
confidence: 99%
“…These compounds play an essential part in the metabolism of kidney and liver, and condensation of amino-acids with aldehydes and keto bodies is well known to take place purely chemically [Schiff, 1901;S0rensen, 1908]. More recently a similar simple condensation has been described by Herbst [1936] between amino-acids and pyruvic acid. Akasi [1937] reports tbe isolation of octopine, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…The results of studies of the reaction between a number of keto acidamino acid combinations (35,38) are summarized in Table I. It should be pointed out that the reaction always led to the formation of racemic products.…”
Section: The Transamination Reaction 77mentioning
confidence: 99%